Diagnostic efficacy of conventional cytological smears and cell block of ascitic fluid for detection of malignant cell - Nowsher, Md Neaz; Karim, Syeda Noorjahan; Karim, Rezwana; Rahman, DM Arifur; Barua, Ashim Ranjan (Mediscope, 2023)
Introduction: For identification of malignant cells in effusion, cell block is a simple, inexpensive method and no additional expatriation is needed. In the identification of malignant cells in effusion, its differentiation from cells showing reactive and degenerative changes were diagnostic difficulties in some of the cases. The cell block method yielded more cellularity and provided better morphological details. Multiple sections could be obtained for special stain and immunohistochemistry when required. Methods: This cross-sectional observational study was carried out at the Department of Pathology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh; from March, 2017 to December, 2018. The sample size was 101 and the study material was ascitic fluids of clinically suspected malignancy cases. Conventional smears and cell block were prepared in every cases. Both conventional and cell block slides were scored according to Miar’s point scoring system and analyzed according to diagnostic categories. Results: By conventional smear, 86 cases were diagnosed as negative for malignancy, four cases were diagnosed as suspicious for malignancy and remaining 11 cases were diagnosed as positive for malignancy. After analyzing cell blocks, three more malignant cases were diagnosed, which had been diagnosed as suspicious for malignancy by conventional smear. Cell block technique showed significant differences in the diagnosis of suspicious cases of effusion in comparison to conventional smear (p<0.05) Conclusion: Cell Block technique could be considered as a useful adjunct in evaluating malignant cells in malignant ascitic effusion for a final cytodiagnosis, along with the routine conventional method. Mediscope 2023;10(1): 01-09